Tracing Errors, Shaping Skills: An Analysis of Maharah al-Kitabah among Arabic Learners - Sukri Wagola; Abdul Qahar Zainal; Akhmad Syahid; Mohammad Zainal Hamdy; Ali Mahmoud Al Asma'i Ismail (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Writing skill (maharah al-kitabah) is one of the essential competencies in Arabic language learning; however, many students still struggle to master it effectively. This study investigates the writing errors made by students of class VIII.3 at MTsN 2 Makassar, with the primary aim of identifying the types of errors and analyzing the underlying causes behind them. Employing a qualitative descriptive approach with an error analysis framework, data were collected through writing tests and semi-structured interviews. The data were then analyzed using techniques of data reduction, data display, and conclusion drawing. The findings reveal that the majority of students continue to encounter significant difficulties in maharah al-kitabah. The types of errors most frequently observed include: improper spacing between words, confusion between similar-looking Arabic letters, misuse of punctuation, incorrect application of tasydid, and the omission or addition of letters within words. Furthermore, the causes of these errors can be classified into internal and external factors. Internal factors consist of limited writing practice, lack of concentration, hurried writing, restricted reading habits, insufficient understanding of Arabic grammar, and a limited vocabulary range. Meanwhile, external factors are associated with the teaching methods used, the broader learning environment, and the influence of parental support. This study contributes to the field of Arabic language education by providing an in-depth understanding of the error patterns in students’ writing. It also emphasizes the need for more targeted instructional strategies, greater emphasis on writing practice, and supportive learning environments to improve maharah al-kitabah among learners.